Nose-to-Brain Delivery of Antiviral Drugs: A Way to Overcome Their Active Efflux? - Alessandro Dalpiaz; Barbara Pavan (MDPI AG, 2018)
Although several viruses can easily infect the central nervous system (CNS), antiviral drugs often show dramatic difficulties in penetrating the brain from the bloodstream since they are substrates of active efflux transporters (AETs). These transporters, located in the physiological barriers between blood and the CNS and in macrophage membranes, are able to recognize their substrates and actively efflux them into the bloodstream. The active transporters currently known to efflux antiviral drugs are P-glycoprotein (ABCB1 or P-gp or MDR1), multidrug resistance-associated proteins (ABCC1 or MRP1, ABCC4 or MRP4, ABCC5 or MRP5), and breast cancer resistance protein (ABCG2 or BCRP). Inhibitors of AETs may be considered, but their co-administration causes serious unwanted effects. Nasal administration of antiviral drugs is therefore proposed in order to overcome the aforementioned problems, but innovative devices, formulations (thermoreversible gels, polymeric micro- and nano-particles, solid lipid microparticles, nanoemulsions), absorption enhancers (chitosan, papaverine), and mucoadhesive agents (chitosan, polyvinilpyrrolidone) are required in order to selectively target the antiviral drugs and, possibly, the AET inhibitors in the CNS. Moreover, several prodrugs of antiretroviral agents can inhibit or elude the AET systems, appearing as interesting substrates for innovative nasal formulations able to target anti-Human Immunodeficiency Virus (HIV) agents into macrophages of the CNS, which are one of the most important HIV Sanctuaries of the body.